A Systematic Review of Healthcare Professionals' Knowledge, Attitudes, and Practices Regarding Adverse Drug Reaction Reporting in Southeast Asia - Maria Sintia Manek; Chairun Wiedyaningsih; Dwi Endarti (Jurnal FARMASIMED (JFM), 2026)
Background: Adverse drug reaction (ADR) reporting is a crucial component of ensuring patient safety within a pharmacovigilance system. ADR reporting plays an essential role in detecting, assessing, and preventing adverse effects related to medications in clinical practice. However, ADR reporting practices in Southeast Asia remain low. Objective:  The purpose of this systematic review was to evaluate and synthesize evidence regarding healthcare professionals' knowledge, attitudes, and practices (KAP) regarding ADR reporting in Southeast Asia. This review aims to provide a comprehensive overview of current evidence and identify key gaps that may affect reporting practices. Methods: We conducted a literature search using PubMed, Scopus, EBSCOhost, and Web of Science for studies published between 2015 and 2025. Studies meeting the inclusion criteria were assessed for quality and analyzed using the PRISMA approach. This systematic review examined 16 studies from six Southeast Asian countries. Results: Most healthcare professionals have positive attitudes toward reporting ADRs, but knowledge varies, and actual reporting practices are low. Training, education, and incentive support were the most frequently cited factors facilitating reporting. Time constraints, unavailability of reporting forms, lack of awareness, uncertainty about the causality of drugs with adverse reactions, and lack of incentives were the main barriers to reporting. Conclusion: Healthcare professionals in Southeast Asia generally show positive attitudes toward ADR reporting, but knowledge remains varied, and reporting practices are low. Continuous education, system integration, and stronger national pharmacovigilance policies are needed to improve reporting.